Phonological assimilation in the English of native and non-native speakers’ reading and spontaneous speech - Mohammad Azannee Haji Saad; Zahariah Pilus (Journal of Modern Languages, 2017)
This study examines the frequency of phonological assimilation in the speech of experienced non-native speakers (L2) of English and native speakers (L1) of British English. The study compares reading and spontaneous speech performance by both groups. Results indicate that the L1 group assimilates more than the L2 group in their speech production although the L2 participants are experienced English language instructors. In addition to studying the frequency of phonological assimilation, this study also compares the occurrences of assimilation across different task types. There is a tendency for assimilation to occur more frequently when the task requires less focus on the words.